(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
With the boom of Smartphone’s and Tablets, Digital Marketing has reached a new high. People who were previously unrelated to the field are now learning about it and are excited for the same. The era has changed does much that if a person does not have a Social Media account; he/she is looked down on. Digital Marketing is the Process of building and maintaining customer relationships through online activities to facilitate the exchange of ideas, products, and services that satisfy the goals of both parties. Both primary and secondary data have been used to achieve the objectives of the study.